Comparative assessment of hemocompatibility of the suture material modified with heparin using different techniques - Т. N. Akentieva; S. V. Luzgarev; Т. V. Glushkova; Yu. А. Kudryavtseva (Сибирский научный медицинский журнал, 2024)
Postoperative complications in surgery, including thrombosis, are often associated with the suture material. The search for new types of suture materials that reduce the risk of vascular anastomotic complications remains an urgent task. The aim of the study was to compare and evaluate the effectiveness of two types of suture materials modified with heparin in terms of the hemocompatibility. Material and methods. The study involved a thread based on the Prolene 3.0 Polypropylene Suture (Ethicon, USA) that had undergone subsequent modification. The suture was modified with either heparin with polydimethylsiloxane or heparin with polyhydroxybutyrate/oxyvalerate. The consistency and hemocompatibility of the modifying layer were evaluated by scanning electron microscopy, diffuse scattering spectroscopy, hemolysis, platelet adhesion and aggregation. Results and discussion. The modifying layer based on heparin and polydimethylsiloxane was nonhomogeneous, with either thick or completely absent coating layer. The modifying layer based on heparin and polyhydroxybutyrate/oxyvalerate was homogeneous, without signs of thickening. Diffuse reflectance spectroscopy confirmed its presence on the thread surface. Evaluation of the hemocompatibility of the modified thread revealed the absence of hemolysis in all the studied groups. The modifying layer based on heparin and polyhydroxybutyrate/ oxyvalerate significantly reduced the maximum platelet aggregation (46.28 %) compared with the unmodified thread (82.64 %), the thread modification with heparin and polydimethylsiloxane did not influence on the indicator (77.72 %). The number of platelets adhered on the surface of the thread modified with heparin and polyhydroxybutyrate/oxyvalerate was insignificant, consisting of single inactivated platelets, in contrast to a thread modified with polydimethylsiloxane rubber and heparin, on the surface of which a large number of adherent activated platelets were found. Conclusions. The results obtained indicate the promising approach for the prevention of postoperative thrombosis by layer-by-layer modification of thread with heparin and polyhydroxybutyrate/oxyvalerate.